Binding of a biosynthetic intermediate to AtrA modulates the production of lidamycin by Streptomyces globisporus. Issue 6 (24th April 2015) - Li, Xingxing; Yu, Tengfei; He, Qing; McDowall, Kenneth J.; Jiang, Bingya; Jiang, Zhibo; Wu, Linzhuan; Li, Guangwei; Li, Qinglian; Wang, Songmei; Shi, Yuanyuan; Wang, Lifei; et al.
Summary The control of secondary production in streptomycetes involves the funneling of environmental and physiological signals to the cluster‐situated (transcriptional) regulators (CSRs) of the biosynthetic genes. For some systems, the binding of biosynthetic products to the CSR has been shown to provide negative feedback. Here we show for the production of lidamycin (C‐1027), a clinically relevant antitumor agent, by Streptomyces globisporus that negative feedback can extend to a point higher in the regulatory cascade. We show that the DNA‐binding activity of the S. globisporus orthologue of AtrA, which was initially described as a transcriptional activator of actinorhodin biosynthesis in S. coelicolor, is inhibited by the binding of heptaene, a biosynthetic intermediate of lidamycin. Additional experiments described here show that S. globisporus AtrA binds in vivo as well as in vitro to the promoter region of the gene encoding SgcR1, one of the CSRs of lidamycin production. The feedback to the pleiotropic regulator AtrA is likely to provide a mechanism for coordinating the production of lidamycin with that of other secondary metabolites. The activity of AtrA is also regulated by actinorhodin. As AtrA is evolutionarily conserved, negative feedback of the type described here may be widespread within the streptomycetes.